Rape culture on campus - Minister, M. Cooper (Lexington Books, 2018)
"This book explores the failures of existing responses to sexual violence on university campuses and advocates for more long-term interventions. Written for educators, administrators, activists, and students, this book exposes the various aspects of rape culture in academic life" --